Remote Terminal Unit Alternatif - Heri Andi (Energi & Kelistrikan, 2022)
Load Breaking Switch (LBS) is an asset that has an important role in the distribution system with the role of disconnecting and connecting the flow of electrical power from a 20 kV distribution system, LBS can also be used as a section when adding or reducing feeder loads and is often used as a maneuvering point between Feeder. To optimize the function and operation of the Motorized LBS, it is necessary to integrate the SCADA system so that it can be operated remotely. In this integration process, one of the important components needed is the Remote Terminal Unit (RTU) which functions as a device that provides information about the equipment and carries out orders (teleinformation), but to achieve this we are constrained by the very expensive price of the RTU. For this reason, an alternative remote terminal unit is needed as a substitute for the RTU which represents the function of the RTU on the scada system itself. By installing alternative RTUs, SAIDI decreased by 17.74 % and recovery time by 2.99 %.